The Trouble with Transfers: An Analysis of the Referral of Uwinkindi to the Republic of Rwanda for Trial - Jennifer Wren Morris (Washington University Law Review, 2012)
This Note will provide a brief overview of the Rwandan genocide, the U.N.’s establishment of the Tribunal, and efforts to bring the Tribunal to a close. It will then examine the transfer applications that preceded Uwinkindi, the shifts in precedent that ultimately led to transfer, and, in conclusion, will assess the wisdom of the transfer itself. This approach focuses on the parallel, but sometimes contravening, goals of maintaining the provision of due process and fairness through the structure of an international court and the preservation and improvement of this process in the courts of the country where the crime occurred.
Keywords: genocide; Rwanda; Prosecutor v. Uwinkindi; transfer applications; due process; international court